Some A Survey Study On The Role of Women in Controlling Parasites Contaminated with Vegetables. (Baghdad Science Journal, 2011)
Three hundred samples of washing water of vegetables were collected from women aged ( 15- 6o) years from different area in Baghdad governorate and its suburbs include two rural area ( Jaddria in Baghdad university and Al –Wagif in Rashdia) and two urbane area (Mansoure and Escan) . The samples were examined by precipitation method and then by staining method ( Lugols –Iodine stain) . The percentage of infection of intestinal parasites 36.3% include 15.3% for urban area and 57.3% in rural area and a significant difference was found between those groups . .The results showed also increased in the prevalence of parasitic infection in group age (15 -30) year .Also the results showed only 109 sample infected with eight species of enteric parasites fife of them are protozoa (Entamoeba histolytica ,Giardia lamblia ,Entamoeba coli, Chilomastix mesnili and Iodamoeba butschlii) and three eggs of helminthes (Taenia saginata) and Nematoda( Ascaris lumbricoides , Trichuris trichura )Also a significant difference was found between prevalence of infection and education state .